2022
DOI: 10.3390/plants11070853
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Differentially Affects the Primary and Secondary Metabolism of Peppers (Capsicum annuum L.) According to the Genotype, Fruit Part, and Salinity Level

Abstract: A total of four Capsicum annuum L. genotypes (‘Caro F1’, ‘Berenyi F1’, ‘Somborka’ and ‘Novosadka’) were exposed to two intensities of salt stress. We observed a significant decrease in the sugar content in all salt stressed treatments, except for the sucrose content of the pericarp of the ‘Caro F1’ cultivar. Salt stress had a largely negative effect on the total and individual organic acid content, although the effect differed among cultivars. Using high performance liquid chromatography coupled with a mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Higher lipid peroxidation is a common phenomenon under salt stress caused by membrane injury, which leads to the production of a number of free oxygen radicals that ultimately disturbed the plants’ functioning and hence the metabolism . Under salt-induced oxidative stress, the excessive synthesis of ROS is controlled either by – OH and O 2 – or by molecular oxygen excitation (O 2 ) to form singlet oxygen. , The plants then abruptly activate their antioxidant potential system, which is principally regulated by SOD, POD, CAT, and APX antioxidant enzymes, in response to the excessive ROS production in order to scavenge the ROS and maintain the redox equilibrium, hence boosting plant development. In addition to enzyme antioxidants, nonenzymatic antioxidants including proline, phenolic, and flavonoids work as secondary metabolites to prevent oxidative stress from salt from causing oxidative damage. Similarly in the current study, the elevated levels of oxidative stress biomarkers were noticed in both Raphanus sativus L. genotypes, which were then reduced by the stimulation of an antioxidant potential system governed by both enzymatic and nonenzymatic antioxidants. Earlier reports also revealed that the higher activities of antioxidants were observed following saline stress in H.…”
Section: Discussionmentioning
confidence: 99%
“…Higher lipid peroxidation is a common phenomenon under salt stress caused by membrane injury, which leads to the production of a number of free oxygen radicals that ultimately disturbed the plants’ functioning and hence the metabolism . Under salt-induced oxidative stress, the excessive synthesis of ROS is controlled either by – OH and O 2 – or by molecular oxygen excitation (O 2 ) to form singlet oxygen. , The plants then abruptly activate their antioxidant potential system, which is principally regulated by SOD, POD, CAT, and APX antioxidant enzymes, in response to the excessive ROS production in order to scavenge the ROS and maintain the redox equilibrium, hence boosting plant development. In addition to enzyme antioxidants, nonenzymatic antioxidants including proline, phenolic, and flavonoids work as secondary metabolites to prevent oxidative stress from salt from causing oxidative damage. Similarly in the current study, the elevated levels of oxidative stress biomarkers were noticed in both Raphanus sativus L. genotypes, which were then reduced by the stimulation of an antioxidant potential system governed by both enzymatic and nonenzymatic antioxidants. Earlier reports also revealed that the higher activities of antioxidants were observed following saline stress in H.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is important to note that, although the distance was shown only for two variables, the distance metric is generalizable for vector spaces of any dimension [ 19 , 25 ]. The difficulty of selecting genotypes through adaptability studies under abiotic stress conditions such as drought, salinity, and aluminum toxicity has been shown in soybean [ 3 , 4 , 5 , 14 , 16 ], sorghum [ 6 ], wheat [ 7 ], and corn [ 11 ]. Several methods are available to evaluate groups of genotypes in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Low water content and salt excess in the soil at sowing time cause delayed and reduced seed germination, unequal seedling emergence, and unsatisfactory stand establishment, which results in crop yield reductions [ 7 , 8 ]. Drought and salinity affect seed germination and seedling growth by creating highly negative water potentials, thus preventing water uptake by the seeds and plants [ 8 , 9 , 10 , 11 ]. Salinity may also cause direct phytotoxic effects of Na + and Cl − ions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…119 Increased levels of NaCl (20−40 mM) enhanced the individual phenol content and the capsaicinoids levels up to 50 times in the pericarps of C. annuum cultivars. 120 The activities of key CBGs like PAL, cinnamic-4-hydroxylase (C4H), CS, and peroxidase (POD) were increased during drought stress in Capsicum cultivars along with the levels of capsaicinoids. 121 Proline treatments and decreased irrigation independently led to increase in total phenolics content in C. annuum.…”
Section: Elicitor Treatment and Mineralmentioning
confidence: 99%